Piano sonatas no. 1-3, op. 2, no. 1-3, reprint of Pleyel edition - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Paris; France; Ice. Pleyel)
Early edition of the Piano sonatas nos. 1-3 in F minor, A major, and C major, op. 2, no. 1-3, Titelauflage of Pleyel's edition originally published by 1803.